Acridine-based ligands from cobalt(II) mediated rearrangement of diphenylamine-based starting materials. Issue 1 (1st February 2016) - Malthus, Stuart J.; Wilson, Rajni K.; Larsen, David S.; Brooker, Sally
Abstract : The synthesis and characterisation of two cobalt(II) complexes, [Co II L Br-acr Cl2 ] (1a ) and [Co II L H -acr Cl2 ] (1b ), with acridine head-units resulting from an unexpected ligand rearrangement from a diphenylamine head-unit, and the intended cobalt(II) complex, Co II L Br-dpa (Cl)(H2 O) (2 ), are reported. Single crystals of the two dark green acridine-based cobalt(II) complexes, 1a and1b, form in a one-pot reaction of cobalt(II) chloride, the chosen diphenylamine-2, 2′-dicarboxaldehyde (Ia 4, 4-′dibromo- orIb unsubstituted), triethylamine and two equivalents of 2, 4-dimethylaniline in acetonitrile, in 23% yield. In contrast, the intended diphenylamine-based complex was isolated in two steps: first isolation of the Schiff base ligand, then complexation with cobalt(II) chloride and deprotonation with potassium tert -butoxide, in methanol/dichloromethane, giving2 as a bright yellow solid in 67% yield. All three complexes feature cobalt(II) centres, with N2 Cl2 approximately tetrahedral coordination for1a and1b confirmed by single crystal structure determinations. It is proposed that after one imine 'arm' forms, cobalt(II) coordination facilitates the other aldehyde undergoing an intramolecular cyclisation to form the new heterocyclic acridine head-unit. The structures of both of the resulting acridine-based complexes, 1a and1b, and that of the originally intended Schiff base ligand, HL Br-dpa, were confirmed by single-crystal X-ray diffraction. These are the first examples of complexes of an acridine ligand of this type.